Забезпечення принципів правової держави і розвиток державно-правового режиму в Україні - Дроботова, Т.Б. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
В статье исследуется специфика взаимосвязи между процессом утверждения в Украине принципов правового государства и развитием государственно-правового режима. Представлен анализ конкретных проблем реализации принципов правового государства в Украине в контексте демократизации государственно-правового режима, развития правовой системы. In article investigates the specificity of interrelation between process of the statement in Ukraine of the state of law principles and development of a regime of state and law. The author gives the analysis of concrete problems of realization of the state of law principles in Ukraine in a context of democratization of the regime of state and law, the development of legal system.